2017
DOI: 10.5465/amle.2016.0039
|View full text |Cite
|
Sign up to set email alerts
|

A Call for Openness in Research Reporting: How to Turn Covert Practices Into Helpful Tools

Abstract: Research articles often give inaccurate information about how researchers developed hypotheses, analyzed data, and drew conclusions. Published articles sometimes report only some of the hypotheses that researchers tested, or some of the statistical analyses that researchers made. Articles often imply that researchers formulated all hypotheses before they examined their data when in fact they added or deleted hypotheses after they made some data analyses.Indeed, such covert practices are so common that new entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Consistent with this view, a recent survey of over 1,500 researchers found that "selective reporting of results" was regarded as the most important factor contributing to irreproducible research (Baker, 2016). In addition, several commentators have argued that HARKing is one of the questionable research practices that reduces the replicability of published effects (e.g., Aguinis, Cascio, & Ramani, 2017;Hollenbeck & Wright, 2017;John et al, 2012;Kerr, 1998;Mazzola & Deuling, 2013;Munafò et al, 2017;Schwab & Starbuck, 2017;Świątkowski & Dompnier, 2017;Unkelbach, 2016;Wagenmakers, Wetzels, Borsboom, & van der Maas, 2011). According to this argument, although many researchers claim to conduct confirmatory tests of a priori hypotheses, they actually conduct multiple exploratory tests that are uncorrected for having a greater chance of detecting false positive results.…”
Section: 166 58%mentioning
confidence: 99%
See 4 more Smart Citations
“…Consistent with this view, a recent survey of over 1,500 researchers found that "selective reporting of results" was regarded as the most important factor contributing to irreproducible research (Baker, 2016). In addition, several commentators have argued that HARKing is one of the questionable research practices that reduces the replicability of published effects (e.g., Aguinis, Cascio, & Ramani, 2017;Hollenbeck & Wright, 2017;John et al, 2012;Kerr, 1998;Mazzola & Deuling, 2013;Munafò et al, 2017;Schwab & Starbuck, 2017;Świątkowski & Dompnier, 2017;Unkelbach, 2016;Wagenmakers, Wetzels, Borsboom, & van der Maas, 2011). According to this argument, although many researchers claim to conduct confirmatory tests of a priori hypotheses, they actually conduct multiple exploratory tests that are uncorrected for having a greater chance of detecting false positive results.…”
Section: 166 58%mentioning
confidence: 99%
“…The second approach is to change the culture of the scientific community so that it is more accepting of exploratory research (e.g., Hollenbeck & Wright, 2017;Schwab & Starbuck, 2017). Such a change is intended to reduce researchers' motivation to engage in undisclosed HARKing.…”
Section: 166 58%mentioning
confidence: 99%
See 3 more Smart Citations